1993
DOI: 10.5014/ajot.47.7.619
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant Wheelchair Accessibility

Abstract: This study was designed to determine the compliance of restaurants to the wheelchair accessibility standards set forth in the Uniform Federal Accessibility Standards. The standards that were operationalized in this study are also found in Title III of the Americans With Disabilities Act of 1990. The data were collected at 120 sites in three midwestern states. For one who uses a wheelchair, parking the car is often an obstacle to eating out. Only 53% of the restaurants surveyed provide handicapped parking. Ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 3 publications
2
18
0
Order By: Relevance
“…Although a number of federal reports 18 -20 and surveys 21 conducted to determine accessibility for PWIs highlight the ADA's achievements in improving access, they continue to report widespread and persistent barriers to employment; education; religious settings; social, cultural, and political participation; transportation; health care; and recreational activities. 21 Access studies conducted of public buildings, 22, 23 restaurants, 24 food stores, 25 businesses 26 and physicians' offices 27,28 consistently report barriers related to the inaccessibility of parking lots, building entrances and restrooms. Other frequently reported barriers include kerb cuts, stairs, ramps, doorways, narrow aisles, handrails, signage, seating and inaccessible controls (push buttons, switches, door knobs).…”
Section: Background and Rationalementioning
confidence: 99%
“…Although a number of federal reports 18 -20 and surveys 21 conducted to determine accessibility for PWIs highlight the ADA's achievements in improving access, they continue to report widespread and persistent barriers to employment; education; religious settings; social, cultural, and political participation; transportation; health care; and recreational activities. 21 Access studies conducted of public buildings, 22, 23 restaurants, 24 food stores, 25 businesses 26 and physicians' offices 27,28 consistently report barriers related to the inaccessibility of parking lots, building entrances and restrooms. Other frequently reported barriers include kerb cuts, stairs, ramps, doorways, narrow aisles, handrails, signage, seating and inaccessible controls (push buttons, switches, door knobs).…”
Section: Background and Rationalementioning
confidence: 99%
“…For food and restaurant services, studies have shown that patrons with disabilities need accessible parking, entrances, restrooms, and dining areas (McClain et al, 1993;McClain & Todd, 1990). However, these needs are not always met in the real world.…”
Section: General Overview Of Travel Needs Of People With Disabilitiesmentioning
confidence: 99%
“…In order to help increase mobility, the Americans with Disabilities Act (ADA) and Architectural Barriers Act developed specific accessibility guidelines for buildings and facilities that must be considered during their design, construction and alteration (ADA 2004). While this is a great improvement, other environmental barriers, especially in outdoor environments, still exist that can prevent wheelchair users from participation and integration into the community (McClain et al 1993, Thapal et al 2004. It is evident that wheelchair users are confronted with a number of impediments to travel and could benefit from an assistive technology that could improve their mobility.…”
Section: Introductionmentioning
confidence: 99%